2021
DOI: 10.12669/pjms.38.1.4562
|View full text |Cite
|
Sign up to set email alerts
|

Journal Club is a way forward to adopt Evidence Based Practice among dental House Officers

Abstract: Objectives: To identify the improvement in knowledge, presentation skills, critical skills and self-directed learning process during Journal Club platform amidst dental house officers of 2018, 2019 and 2020 after completing one year house job training at Bahria dental College Karachi. Methods: This cross-sectional study was conducted from Dec- 2018 till Dec-2020. The six items were asked about perception of change for evidence-based process of (knowledge, cognitive, affective and participant domains) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Another study at the University of Newcastle Medical School in 2001 suggested teaching critical evaluation to third-year students for only three weeks utilizing a JC and letter-writing strategy [8]. Only a few studies using EBM curricula have been reported in the literature, and these were largely for PGs and residents [5,6,20]. Furthermore, no consistent assessment approach or instrument was used in any of the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study at the University of Newcastle Medical School in 2001 suggested teaching critical evaluation to third-year students for only three weeks utilizing a JC and letter-writing strategy [8]. Only a few studies using EBM curricula have been reported in the literature, and these were largely for PGs and residents [5,6,20]. Furthermore, no consistent assessment approach or instrument was used in any of the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increased workload and time required to comprehend such concerns, there was a drop in self-reported behavior and dissatisfaction. Only a few studies using EBM curricula have been reported in the literature, and these were largely for PGs and residents [ 5 , 6 , 20 ]. Furthermore, no consistent assessment approach or instrument was used in any of the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation